Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread. (27th February 2021) - Cunningham, Calum X.; Comte, Sebastien; McCallum, Hamish; Hamilton, David G.; Hamede, Rodrigo; Storfer, Andrew; Hollings, Tracey; Ruiz‐Aravena, Manuel; Kerlin, Douglas H.; Brook, Barry W.; Hocking, Greg; Jones, Manna E.
Abstract: Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance. Abstract : Tasmanian devil facial tumour disease (DFTD) provides the opportunity to study an emerging epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. The spatial spread of DFTD was most rapid through high‐density areas, causing 82% local declines in density and reducing the wild population to just 16 900 individuals.